Building resilient landscapes in a semi-arid watershed: Anthropogenic and natural burning histories in Late Holocene Tesuque Creek, northern New Mexico. (December 2022) - Damick, Alison; Krause, Samantha; Rosen, Arlene
As mega-fires have swept the North American West in recent decades, studies of past fire events have gained academic interest. Deep-time perspectives are necessary to better understand the periodicity of fire events and to identify basic drivers of frequent fire episodes through time, including potential anthropogenic fire use. Our study contributes to the growing field of archeological fire ecology in the Southwest with an examination of a high-resolution geobotanical dataset for Holocene fire regimes as indicated within sediments from an alluvial section from Tesuque Creek in northern New Mexico. Using phytolith, geochemical, and sedimentological data, we reconstruct indices for burn cycle seasonality and destabilization of riparian vegetation communities that suggest potential anthropogenic land use and possible patterns distinguishing human burning from lightning ignitions. Through this study, we consider the potential role of hunter-gatherer behavior in producing fire landscapes as part of their strategies for managing risks in the fragile environments of the Middle-Late Holocene in northern New Mexico. We suggest that combining geo and botanical datasets from alluvial sections with archeological evidence will allow researchers to fine-tune the resolution of local climate sequences and their environmental impacts on small landscape scales. When such small-scale studies can be aggregated, they may further contribute to testing models of regional patch-burning, either natural or anthropogenic. We further posit that human relationships with fire in the past should be considered as collaborative efforts with lightning-ignited burns, to manage the risks associated with both too much and too little fire in fragile dryland ecosystems.